Generating Electricity through Waste Burners: An Alternative Solution for Reducing Waste - Anggraeni, Ratih; ., Ramadani; Najib Mauludi, Muhammad; Al-Maududi, Affan; Rifqi Saifullah, Muhammad; Al-Irsyad, Muhammad (KnE Life Sciences, 2021)
Waste is a wordlwide problem including in Indonesia. The increasing amount of waste is caused by the increasing human population. Proper waste management must be applied to avoid detrimental health and environmental consequences. One way to manage waste is to design a device that could convert waste into electrical energy. This research aimed to provide a solution so that the volume of waste in Indonesia can be reduced and used as renewable energy. The methods used in this research were (1) identifying previous research on waste incineration and (2) designing a waste incinerator as appropriate technology and equipped with a system of utilizing the generated heat into electrical energy. The result of this research is the design of a device that can produce electricity from smoke and thereby reduce air pollution. Smoke from waste burning in a furnace was first filtered using a carbon cloth material to reduce air pollution. The heat from combustion was used to boil the water and change it into fumes above 100ºC. The steam produced had potential energy which was converted into kinetic energy through a turbine that can move the shaft to produce mechanical energy. Mechanical energy was then used to rotate the generator shaft that generated electric current and was then used to charge the battery. The battery power was then distributed for regualr use using a power converter. Keywords: combustion, design, electricity, environment, health, waste